2017
DOI: 10.9790/3008-1203036275
|View full text |Cite
|
Sign up to set email alerts
|

Action of Melatonin on Severe Acute Liver Failure in Rats

Abstract: Abstract:Severe acute liver failure (ALF) manifests itself as a rare syndrome, with multiple etiologies for similar clinical conditions. Melatonin (MLT) is a lipophilic indolamine that is synthesized in the pineal gland from serotonin. This study was designed to evaluate hepatic changes resulting from the thioacetamide-induced ALF model, as well as the effects of MLT treatment in male Wistar rats (n = 56) in 24-and 48-h experiments. The results indicate a hepatoprotective effect of MLT, with no difference betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
(56 reference statements)
6
2
0
Order By: Relevance
“…Gln reduced serum levels of AST, ALT, and ALP, while significantly increased levels of these enzymes were found in animals in the TAA group, suggesting massive hepatic impairment after exposure to the xenobiotic. In other studies, Gln was also able to decrease serum levels of these enzymes, thus corroborating our findings[7,14,46].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Gln reduced serum levels of AST, ALT, and ALP, while significantly increased levels of these enzymes were found in animals in the TAA group, suggesting massive hepatic impairment after exposure to the xenobiotic. In other studies, Gln was also able to decrease serum levels of these enzymes, thus corroborating our findings[7,14,46].…”
Section: Discussionsupporting
confidence: 92%
“…We also observed an increase in TBARS levels in the livers of animals in the TAA group, which is indicative of increased lipid peroxidation. Other authors found similar increases in TBARS in studies that used TAA to induce liver damage[6,7,43]. Again, Gln administration was able to reduce these levels in our animals, corroborating the findings of several other studies that have demonstrated its protective effect in different experimental models[21,26,47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our research group has conducted studies on the effects of MLT on liver injury and diseases and found that MLT can regulate various molecular pathways such as inflammation, proliferation, apoptosis, metastasis, and autophagy in different situations. 46,49,50 Here, our results suggest that MLT has a powerful antifibrogenic effect, modulating the parameters of oxidative stress, angiogenesis, and inflammation. The action of MLT on the improvement of liver fibrosis seems to make it a promising candidate for clinical trials in chronic liver diseases associated with increased fibrogenesis.…”
Section: Discussionsupporting
confidence: 51%
“…Our research group has conducted studies on the effects of MLT on liver injury and diseases and found that MLT can regulate various molecular pathways such as inflammation, proliferation, apoptosis, metastasis, and autophagy in different situations …”
Section: Discussionmentioning
confidence: 99%